Sprache(n) der Geschichte. Kooperation des Modellprojekts ProDaZ mit der Geschichtsdidaktik des Historischen Instituts der Universität Duisburg-Essen - Altun, Tülay; Bernhardt, Markus; Günther, Katrin (Deutsch als Zweitsprache in der Lehrerbildung. Bd. 2)

Kommentierte Liste von Lehrwerken und Unterrichtsmaterialien für neu zugewanderte Schülerinnen und Schüler - Frenzel, Beate; Gonas, G.; Günther, Katrin; Strobl, J.; Trianti, D.

Schreibberatung und Schreibförderung. Impulse aus Theorie, Empirie und Praxis

Fast and conspicuous? Quantifying salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Advances in Cognitive Psychology)
Particular differences between an object and its surrounding cause salience, guide attention, and improve performance in various tasks. While much research has been dedicated to identifying which feature dimensions contribute to salience, much less regard has been paid to the quantitative strength of the salience caused by feature differences. Only a few studies systematically related salience effects to a common salience measure, and they are partly outdated in the light of new findings on the time course of salience effects. We propose Bundesen’s Theory of Visual Attention (TV A) as a theoretical basis for measuring salience and introduce an empirical and modeling approach to link this theory to data retrieved from temporal-order judgments. With this procedure, TV A becomes applicable to a broad range of salience-related stimulus material. Three experiments with orientation pop-out displays demonstrate the feasibility of the method. A 4th experiment substantiates its applicability t
Keywords: salience; visual attention; Bayesian inference; theory of visual attention; computational modeling; Visual Attention; Computational Modeling; Inference; Judgment; Statistical Probability

Peripheral visual cues: Their fate in processing and effects on attention and temporal-order perception. - Tünnermann, Jan; Scharlau, Ingrid (Frontiers in Psychology)
Peripheral visual cues lead to large shifts in psychometric distributions of temporal-order judgments. In one view, such shifts are attributed to attention speeding up processing of the cued stimulus, so-called prior entry. However, sometimes these shifts are so large that it is unlikely that they are caused by attention alone. Here we tested the prevalent alternative explanation that the cue is sometimes confused with the target on a perceptual level, bolstering the shift of the psychometric function. We applied a novel model of cued temporal-order judgments, derived from Bundesen’s Theory of Visual Attention.We found that cue–target confusions indeed contribute to shifting psychometric functions. However, cue-induced changes in the processing rates of the target stimuli play an important role, too. At smaller cueing intervals, the cue increased the processing speed of the target. At larger intervals, inhibition of return was predominant. Earlier studies of cued TOJs were insensitive
Keywords: cueing; temporal-order judgements; theory of visual attention (TVA); peripheral cue; processing speed; stimulus encoding; prior entry; Attention; Cues; Face Perception; Judgment

(Un)diszipliniertes Schreiben? Schreiben lehren und lernen im Studium und in den Fächern an der Leuphana Universität - Heß, Christiane; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

"Das zu riskieren, ist schon eine große Tat": Ludwig Huber im Gespräch mit Ingrid Scharlau - Huber, Ludwig; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Attention, awareness, discipline, and effort: Die Liberal Arts und ein College in Deutschland - Beck, Karin; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Die Vergnügungen der anderen: Fachsensible Hochschuldidaktik als neuer Weg zwischen allgemeiner und fachspezifischer Hochschuldidaktik - Scharlau, Ingrid; Keding, Gesche (Pädagogische Hochschulentwicklung: von der Programmatik zur Implementierung)

Sich gar nicht erst im behaglichen Zuhause der eignen Disziplin einrichten: Eine fachfremde Hausarbeit im ersten Semester - Scharlau, Ingrid; Heß, Christiane (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

And now for something completely different - Lehren und Lernen angesichts digitaler Herausforderungen - Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Mathematik schreiben - Scharlau, Ingrid (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2014)

Drei Einflüsse auf Schreibberatung und ein integriertes Modell der Selbststeuerung für Schreibberaterinnen und Schreibberater - Keding, Gesche; Scharlau, Ingrid (Schreibberatung und Schreibförderung. Impulse aus Theorie, Empirie und Praxis)

Reading mathematical texts with philosophical methods - Schnieder, Jörn; Scharlau, Ingrid (Special Issue: The Philosophy of Mathematics Education at ICME 13)
The paper presents a hermeneutic approach to teaching and learning mathematics in which the hermeneutic circle is translated into methods of reading mathematical texts with the help of the three decisive steps 1) making prior knowledge explicit, 2) interpreting texts, and 3) fusing horizons of prior understanding and text content.

Zwei Fenster mit verschiedener Sicht - Scharlau, Ingrid; Karsten, Andrea; Nettingsmeier, Pia; Golombek, Christiane; Schäfer, Stefanie (Akademisches Schreiben. Halbband 1: Vom Qualitätspakt Lehre geförderte Schreibzentren und Schreibwerkstätten)

Structure of counterflow flame of ultrahigh-molecular-weight polyethylene with and without triphenylphosphate - Korobeinichev, O.P.; Gonchikzhapov, M.B.; Paletsky, A.A.; Tereshchenko, A.G.; Shmakov, A.G.; Gerasimov, I.E.; Knyazkov, D.A. (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Counterflow flames of ultrahigh-molecular-weight polyethylene with and without triphenylphosphate - Korobeinichev, O.P.; Gonchikzhapov, M.B.; Paletsky, A.A.; Tereshchenko, A.G.; Shundrina, I.K.; Kuibida, L.V.; Shmakov, A.G.; Hu, Y. (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Structure of Ultrahigh Molecular Weight Polyethylene-Air Counterflow Flame (Физика горения и взрыва)
Keywords: Process Chemistry and Technology; Mechanical Engineering

Using text analytics to derive customer service management benefits from unstructured data - Müller, Oliver; Debortoli, S.; Junglas, I.; vom Brocke, J. (MIS Quarterly Executive)
Deriving value from structured data is now commonplace. The value of unstructured textual data, however, remains mostly untapped and often unrecognized. This article describes the text analytics journeys of three organizations in the customer service management area. Based on their experiences, we provide four lessons that can guide other organizations as they embark on their text analytics journeys.

Disentangling the Relationship Between the Adoption of In-Memory Computing and Firm Performance - Fay, Maria; Müller, Oliver; vom Brocke, Jan (European Conference on Information Systems)
Recent growth in data volume, variety, and velocity led to an increased demand for high-performance data processing and analytics solutions. In-memory computing (IMC) enables organizations to boost their information processing capacity, and is widely acknowledged to be one of the leading strategic technologies in the field of enterprise systems. The majority of technology vendors now have IMC technologies in their portfolio, and the interest of companies in adopting such solutions in order to benefit from big data is increasing. Although there is first research on the business value of IMC in the form of case studies, there is a lack of large-scale quantitative evidence on the positive effect of such solutions on firm performance. Based on a unique panel data set of IMC adoption information and financial firm performance data for a sample of companies from the Fortune 500 list this study aims at explaining the relationship between the adoption of IMC solutions and firm performance. In this research-in-progress paper we discuss the theoretical background of our work, describe the proposed research design, and develop five hypotheses for later testing. Our work aims at contributing to the research streams on IT business value and business analytics by helping to better understand the nature of the interdependencies between IMC adoption and firm performance.